Microstructural Mechanisms of Sugarcane Bagasse Biodegradation by Locally Isolated Tropical Cellulolytic Fungi for Environmentally Friendly Composting - Nurhaida Widiani; Ovi Prasetya Winandari (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Sugarcane bagasse is a highly recalcitrant lignocellulosic residue that decomposes slowly under natural conditions, requiring an effective biological agent to accelerate composting. This study evaluated the effectiveness of locally isolated tropical cellulolytic fungi in enhancing bagasse biodegradation based on macromorphological changes and microstructural evidence obtained through Scanning Electron Microscopy (SEM). Four treatments were tested: uninoculated control (P0), single inoculum A (P1), single inoculum B (P2), and consortium A+B (P3), with composting conducted for 56 days under a modified Takakura system. The consortium treatment (P3) exhibited the most advanced compost maturity, characterized by darker coloration, brittle texture, granular structure, and a distinct earthy odor. SEM micrographs further confirmed the greatest extent of lignocellulose breakdown in P3, showing deep longitudinal fissures, fibril delamination, lumen collapse, high porosity, and dense hyphal and spore colonization. These findings indicate that the consortium of cellulolytic fungi accelerates lignocellulose depolymerization through synergistic extracellular enzymatic activity, leading to faster decomposition than single isolates. Overall, the results highlight the bioconversion potential of indigenous tropical fungal consortia as environmentally friendly bioactivators for sustainable management of sugarcane bagasse and other lignocellulosic wastes.